2012
DOI: 10.1038/aps.2012.73
|View full text |Cite
|
Sign up to set email alerts
|

Vam3, a derivative of resveratrol, attenuates cigarette smoke-induced autophagy

Abstract: Aim: To appraise the efficacy of Vam3 (Amurensis H), a dimeric derivative of resveratrol, at inhibiting cigarette smoke-induced autophagy. Methods: Human bronchial epithelial cells were treated with cigarette smoke condensates, and a chronic obstructive pulmonary disease (COPD) model was established by exposing male BALB/c mice to cigarette smoke. The protein levels of the autophagic marker microtubule-associated protein 1A/1B-light chain 3 (LC3), Sirtuin 1 (Sirt1), and foxhead box O 3a (FoxO3a) were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…This supports our finding that autophagy induction can control CSinduced emphysema in subjects with COPD. The sequential investigation of the role of autophagy in CS-induced COPD-emphysema in this study clarifies that CS in fact impairs autophagy, in contrast to the findings of a previous report (44,76). Moreover, a recent study demonstrated the efficacy of CBZ in controlling hepatic fibrosis caused by ATZ mutation (45), which is also known to develop emphysema in a small population (5%) of subjects with COPD, suggesting its potential to also control ATZ-related emphysema.…”
Section: Copdemphysema Pathogenesissupporting
confidence: 77%
“…This supports our finding that autophagy induction can control CSinduced emphysema in subjects with COPD. The sequential investigation of the role of autophagy in CS-induced COPD-emphysema in this study clarifies that CS in fact impairs autophagy, in contrast to the findings of a previous report (44,76). Moreover, a recent study demonstrated the efficacy of CBZ in controlling hepatic fibrosis caused by ATZ mutation (45), which is also known to develop emphysema in a small population (5%) of subjects with COPD, suggesting its potential to also control ATZ-related emphysema.…”
Section: Copdemphysema Pathogenesissupporting
confidence: 77%
“…SIRT1 and FoxO proteins may work synergistically to protect cells. Increased FoxO3a and SIRT1 activity with a reduction in autophagy limits oxidative stress in human bronchial epithelial cells exposed to cigarette smoke condensates (247). Loss of the forkhead transcription factors FoxO1 and FoxO3 in combination with decreased SIRT1 activity during oxidative stress leads to a reduction in autophagy and subsequent chondrocyte cell death, suggesting that SIRT1 with FoxO proteins may be required for cellular protection during oxidative stress (248).…”
Section: Signaling Pathways Of Erythropoietinmentioning
confidence: 99%
“…Yet, FoxO cell protection may not always be directly tied to the induction of autophagy. Up-regulation of FoxO3 and SIRT1 with a reduction in autophagy occurs in human bronchial epithelial cells exposed to cigarette smoke condensates in the presence of the anti-oxidant Amurensis H (Vam3), a dimeric derivative of resveratrol, that can reduce oxidative stress (184). …”
Section: Foxo Proteins Oxidative Stress Apoptosis and Autophagymentioning
confidence: 99%